Insulation sheet between battery cells for electric vehicles
A heat insulating sheet for electric vehicle battery cells, with strategically designed surface properties, addresses the issue of powder falling and maintains high insulation performance by utilizing silica aerogel and fibers.
Patent Information
- Application Number
- JP2025024945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-10-29
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Conventional heat insulating materials containing silica aerogel suffer from low mechanical strength and powder falling due to stress and vibration, which can lead to reduced insulation performance.
The development of a heat insulating sheet for electric vehicle battery cells, featuring silica aerogel and fibers, with one surface having a higher number of holes or larger surface roughness to capture and retain the aerogel, while the other surface has a lower number of voids or smaller surface roughness to minimize peeling and powder falling.
This solution effectively prevents powder falling and maintains high thermal insulation performance by addressing the mechanical strength and retention issues of silica aerogel in heat insulating materials.
Smart Images

Figure 0007670939000004 
Figure 0007670939000005 
Figure 0007670939000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an insulating sheet between battery cells for electric vehicles. [Background technology]
[0002] Silica aerogel is a material made up of a skeleton of multiple silica particles linked together, with pores between the skeleton that are smaller than the mean free path of air. This fine porous structure gives it low thermal conductivity, making it useful as a component material for insulation in automotive parts, residential building materials, industrial equipment, etc.
[0003] Insulating materials containing silica aerogel often have low mechanical strength on the surface, and the problem is that they tend to fall off due to impact. For example, when used as insulating materials for automobile batteries, they may fall off due to pressure caused by the expansion of the battery due to heat, which may degrade the performance of electronic devices. As a solution to this problem, for example, Patent Documents 1 and 2 disclose that the occurrence of powder falling can be suppressed by blending fibrous mineral fibers and hot melt powder in a sheet containing silica aerogel, sealing the surface with a film, etc. In addition, Patent Document 3 discloses that powder falling can be suppressed by providing an insulating elastic member including an elastic layer on one side of a silica aerogel sheet and providing a cover layer on the other side, or by covering the sheet and the entire sheet with an exterior body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2024-97328 A [Patent Document 2] JP 2023-132944 A [Patent Document 3] JP 2023-35097 A Summary of the Invention [Problem to be solved by the invention]
[0005] Among the above-mentioned conventional techniques, the technique of forming a film does not aim to prevent the silica aerogel, which is physically and chemically bonded to the fiber, from falling off (hereinafter referred to as powder falling) when stress is applied to the silica aerogel sheet. Also, according to the technique of Patent Document 2, the hardened layer formed by the hot melt powder may reduce the heat insulating performance of the sheet.
[0006] Among the sheet surfaces, those that are subject to stress caused by the expansion of the battery and those that are close to the source of vibration tend to easily suffer from powder falling off due to the transmission of stress and vibration. If powder falling off of the aerogel occurs, the amount of aerogel present inside the insulation sheet will vary, and there is a risk that the insulation performance will not be fully realized in some areas.
[0007] An object of the present invention is to provide an insulating sheet for insulating between battery cells of an electric vehicle, which contains silica aerogel and is capable of preventing powder falling off. [Means for solving the problem]
[0008] In order to solve the above problems, the present inventors focused on the surface properties of the heat insulating sheet. That is, by adjusting the surface properties of each of the two surfaces when the sheet is viewed horizontally, such as the number (distribution) of voids, the shape of surface roughness, etc., and the ratio thereof on the two surfaces within a predetermined range, one surface has a relatively large number (distribution) of voids or a relatively large surface roughness, and the other surface has a relatively small number (distribution) of voids or a relatively small surface roughness. As a result, it was confirmed that even if the silica aerogel that was physically and chemically bonded to the fiber peels off when stress, vibration, etc. is applied to the silica aerogel sheet, one side has a large number (distribution) of voids or a relatively large surface roughness, making it easy to capture the peeled silica aerogel and preventing powder from falling to the bottom. On the other hand, since the stress and vibration applied to the silica aerogel sheet is small, the silica aerogel that is physically and chemically bonded to the fiber is difficult to peel off. Considering this, it was confirmed that the number (distribution) of voids that cause powder falling off can be reduced, or the surface roughness can be made relatively small. This can prevent powder from falling off of the entire sheet, preventing a decrease in heat insulation performance. In addition, the surface with a relatively large number (distribution) of pores or a relatively large surface roughness has a specific shape and / or is made of fibers, which can increase adhesion to films, etc., and therefore prevent the silica aerogel from peeling off from films, etc. when stress, vibration, etc. are applied to the silica aerogel sheet, thereby preventing powder from falling off to the bottom. As a result, it was found that the sheet's insulation performance could be maintained at a high level.
[0009] The present invention provides the following [1] to
[12] . [1] A material including silica aerogel and fibers, A plurality of voids are provided on one surface and the other surface in the thickness direction, An insulation sheet between battery cells for electric vehicles, in which the ratio of the number of voids on one surface to the number of voids on the other surface is 1.3 or more. [2] The number of holes on the one surface is 25,000 to 225,000 / m 2 The sheet according to [1], [3] The number of holes on the other surface is 10,000 to 50,000 / m 2 The sheet according to [1] or [2], [4] The sheet according to any one of [1] to [3], wherein the difference between the surface roughness Sa of the one surface and the surface roughness Sa of the other surface is 10 μm or more. [5] The sheet according to any one of [1] to [4], wherein the difference in surface roughness Sa between the one surface and the other surface is 30 μm or more. [6] The sheet according to any one of [1] to [5], wherein the surface roughness Sa of the one surface is 60 μm or more. [7] The sheet according to any one of [1] to [6], wherein the surface roughness Sa of the one surface is 80 to 100 μm. [8] The sheet according to any one of [1] to [7], wherein the surface roughness Sa of the other surface is less than 60 μm. [9] The sheet according to any one of [1] to [8], wherein the surface roughness Sa of the other surface is 30 to 50 μm.
[10] The sheet according to any one of [1] to [9], further comprising a film covering at least a portion of the one surface and the other surface.
[11] The sheet according to any one of [1] to [9], further comprising an elastic layer laminated on at least a portion of the one surface and the other surface.
[12] The sheet according to any one of [1] to [9], further comprising a film covering the one side and the other side, and an elastic layer laminated to the one side or the other side via the film. Effect of the Invention
[0010] According to the present invention, it is possible to provide an insulating sheet for electric vehicle batteries that can prevent powder falling and exhibit good thermal insulation properties. That is, according to the present invention, since it is possible to suppress the occurrence of powder falling by dealing with the difference in stress on both sides of the sheet, it is possible to improve the insulating performance of the sheet as a whole, and it is useful as an insulating sheet between battery cells for electric vehicles. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram showing an example of an image obtained when one surface (surface A) of the sheet of the present invention is binarized. [Diagram 2] FIG. 2 is a diagram showing an example of an image obtained when the other surface (surface B) of the sheet of the present invention is binarized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Next, an embodiment of the present invention will be described in detail, although the present invention is not limited to this embodiment.
[0013] In this specification, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y".
[0014] In the present specification, with respect to the numerical ranges described in stages, unless otherwise specified, the upper limit or lower limit of a certain stage of the numerical range can be arbitrarily combined with the upper limit or lower limit of another stage of the numerical range. In addition, in the numerical ranges described in the present specification, the upper limit or lower limit of the numerical range can be replaced with the value shown in the examples.
[0015] In this specification, "X and / or Y (X and Y are optional)" means at least one of X and Y, unless otherwise specified, and means X only, Y only, or X and Y.
[0016] [1. Materials for insulation sheets] The heat insulating sheet is a sheet having silica aerogel and fibers.
[0017] [1.1 Silica aerogel] In this specification, silica aerogel refers to a structure formed by a skeleton mainly composed of secondary particles formed by aggregation of silica fine particles as primary particles, and pores between the secondary particles.
[0018] -Average particle size of primary particles- The diameter of the silica fine particles (primary particles) that form the skeleton of silica aerogel is usually about 2 to 5 nm.
[0019] In this specification, the average particle size is the median size (D50) determined from the volume-based particle size distribution measured by a laser diffraction / scattering method.
[0020] -Pore size- The pores in silica aerogel are usually mostly mesopores. Mesopores have a diameter of 50 nm or less, which is smaller than the mean free path of air. Therefore, air convection is restricted and heat transfer is inhibited, thereby providing excellent heat insulation performance. There is no particular lower limit, but a diameter of 10 nm or more is preferable.
[0021] The shape of the silica aerogel is not particularly limited, and may be spherical, irregularly shaped chunks, etc. For example, in the case of a spherical shape, it is easy to form close packing, so the amount of silica aerogel can be increased, and the effect of improving the heat insulation is increased.
[0022] -Average diameter of secondary particles- The average particle size of the particles (mainly secondary particles) constituting the silica aerogel is usually 1 μm or more, preferably 10 μm or more. The larger the particle size, the smaller the surface area and the larger the pore volume, so that the effect of improving the heat insulation can be improved. The upper limit is not particularly limited, but is, for example, 200 μm or less. The average particle size can be measured by observation with an electron microscope.
[0023] The heat insulating sheet may contain one type of silica aerogel or two or more different types of silica aerogel, and preferably contains two or more types of silica aerogel with different particle sizes, which allows the small-diameter silica aerogel to fill the gaps between the large-diameter silica aerogel, thereby increasing the filling amount and further improving the heat insulating properties.
[0024] The silica aerogel may be formed by impregnating fibers with a liquid (including a slurry) coating solution containing a binder, which will be described later, and drying the fibers. Alternatively, the silica aerogel may be impregnated into fibers in a sol state, which is a precursor of the silica aerogel, and then gelled by heating or the like, and then dried to form the silica aerogel.
[0025] The silica aerogel may be appropriately synthesized or may be a commercially available product.
[0026] [1.2 Fibers (reinforcing fibers)] Examples of the fibers include inorganic fibers such as glass fibers, ceramic fibers, quartz fibers, alumina fibers, silica fibers, silicon carbide fibers, boron fibers, and metal fibers (e.g., aluminum and iron); and organic fibers such as polyamide fibers, polyimide fibers, aromatic polyamide fibers (aramid fibers), polyolefin fibers (e.g., polyethylene fibers, polypropylene fibers), fluorine fibers (e.g., polytetrafluoroethylene fibers), acrylic fibers, polyparaphenylene benzobisoxazole (PBO) fibers, polyarylate fibers, nylon fibers, polyurethane fibers, polyamide fibers, polyether ether ketone (PEEK) fibers, polyether sulfone (PES) fibers, polyether imide (PEI) fibers, polyether ketone (PEK) fibers, and polyphenylene sulfide (PPS) fibers. The fibers may be natural fibers such as wood fibers, silk, hemp, and wool fibers. Among these, fibers having strength and / or heat resistance are preferred, inorganic fibers are more preferred, and glass fibers are even more preferred. The fibers are any one of discontinuous fibers, multiple bundles, and cloth such as nonwoven fabric and woven fabric, or a combination thereof. The fibers contained in the heat insulating sheet preferably include cloth, more preferably nonwoven fabric. This can further improve the mechanical strength. By using a cloth (preferably a nonwoven fabric, more preferably a glass nonwoven fabric) that has been perforated and fluffed as the fibers, the void ratio and surface roughness of the sheet surface can be easily adjusted.
[0027] [1.3 Optional components] The heat insulating material may contain optional components other than the silica aerogel and the fibers, such as a binder and a thickener.
[0028] -binder- The addition of a binder can reduce deterioration in a high-temperature atmosphere and suppress cracks. The binder may be either an inorganic material or an organic material. Examples of inorganic materials include talc, carbon black, kaolinite, montmorillonite, mica, silica (e.g., precipitated silica, gel silica, fused silica), wollastonite, magnesium silicate, titania, metal carbides (e.g., silicon carbide, titanium carbide, or tungsten carbide), metal oxides (e.g., manganese oxide, nickel oxide, tin oxide, silver oxide, bismuth trioxide, chromium oxide, iron oxide, alumina, zirconia, manganese dioxide), metal nitrides (e.g., silicon nitride, aluminum nitride), ilmenite, zirconium silicate, potassium titanate), glass flakes, water glass (sodium silicate), calcium carbonate, barium sulfate, hydraulic materials (e.g., cement, gypsum, magnesium silicate), quicklime, and combinations of slaked lime. Among these, an appropriate material can be selected as needed. For example, silica is preferred because it is easily compatible with silica aerogel, inexpensive, and readily available. In addition, the hydraulic material is preferable because it can form a high-strength heat insulating layer by reacting with water, which is a solvent usually used in the production of silica aerogel, and by filling the gaps between silica particles and forming a binder, and it is inexpensive and easy to obtain. In addition, a material having a large specific surface area and hardness may be selected.
[0029] The organic material is preferably an aqueous binder (a binder that can be dissolved or dispersed in water (can form an emulsion)), and may be a substance that imparts hydrophilic groups to the silica aerogel, or may be a so-called surfactant.
[0030] The glass transition temperature (Tg) of the organic material is preferably −5° C. or lower, and more preferably −20° C. or lower, which can improve adhesion to silica aerogel, improve flexibility of the sheet, and suppress cracks.
[0031] Examples of the binder, which is an organic material, include resins such as acrylic resin, urethane resin, and a mixture of acrylic resin and urethane resin; and rubbers such as styrene butadiene rubber (SBR), nitrile rubber, silicone rubber, urethane rubber, and acrylic rubber, with urethane resin and SBR being preferred. This can improve the flexibility of the sheet, and a flexible sheet can be realized. When using a binder, a crosslinking agent may be used in combination. This can crosslink the binder, and the strength of the sheet can be further improved.
[0032] -Thickener- By using a thickener, it is possible to improve the dispersibility of silica aerogel in a solvent (usually water) and improve processability. It is also possible to impart flexibility to the sheet and suppress cracking. Examples of thickeners include polysaccharides such as carboxymethyl cellulose (CMC), polyethylene oxide (PEO), carboxyethyl cellulose, carboxypropyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, xanthan gum, agarose, carrageenan, and glucomannan; and polyvinyl alcohol.
[0033] -Flame retardants- The flame retardancy of the sheet can be improved by using a flame retardant. Examples of the flame retardant include halogen-based, phosphorus-based, and metal hydroxide-based flame retardants, and phosphorus-based flame retardants (e.g., ammonium polyphosphate, red phosphorus, and phosphate ester) are preferred, water-insoluble phosphorus-based flame retardants are more preferred, and ammonium polyphosphate is even more preferred.
[0034] The optional components are not limited to the above-mentioned components, and may include, for example, one or more selected from the group consisting of preservatives, colorants, infrared shielding particles, and radiation absorbing / reflecting materials.
[0035] [1.4 Composition] -Silica aerogel content- The content of silica aerogel in the heat insulating sheet is usually 10% by mass or more, preferably 20% by mass or more, more preferably 30% by mass or more, based on the total mass of the heat insulating sheet (100% by mass). This allows the heat insulating effect to be more effectively exhibited. The upper limit is usually 60% by mass or less, preferably 50% by mass or less, more preferably 40% by mass or less. This allows the mechanical strength to be prevented from decreasing, and the so-called powder falling can be prevented.
[0036] - Fiber content - The fiber content in the heat insulating sheet is usually 20% by mass or more, preferably 30% by mass or more, based on the total mass of the heat insulating sheet (100% by mass). This can further improve the mechanical strength. The upper limit is usually 70% by mass or less, preferably 60% by mass or less. This can provide mechanical strength commensurate with the content.
[0037] [2. Thermal insulation sheet] The heat insulating sheet is preferably made of the above-mentioned materials and satisfies one or more of the following shapes and physical properties.
[0038] [2.1 Sheet thickness] The heat insulating sheet is usually flat. The thickness of the sheet is not particularly limited, but is, for example, 10 mm or less, 8 mm or less, 3 mm or less, 2.5 mm or less, or 2 mm or less. This allows the strength of the sheet to be maintained within a moderate thickness range. The lower limit is usually 0.1 mm or more, preferably 0.5 mm or more, 1 mm or more. The thickness is preferably approximately uniform, and the thickness variation may be, for example, 5% or less, 4% or less, or 3% or less.
[0039] [2.2 Surface Shape] The heat insulating sheet has irregularities, holes (openings), etc. on its surface (one side and the other side when viewed horizontally). Usually, a plurality of holes are open, and they may be present randomly. The shape of the holes is not particularly limited, and may be circular, polygonal, or irregular. Usually, the irregularities are not uniform, and may be present unevenly.
[0040] The properties of the sheet surface are different between the two surfaces of the sheet, that is, between one side and the other side when viewed in the thickness direction of the sheet. As a result, for example, one side (hereinafter referred to as surface A) with a relatively large number (distribution) of voids or a relatively large surface roughness can easily capture the exfoliated silica aerogel even if the silica aerogel that is physically or chemically bonded to the fiber peels off when stress, vibration, etc. is applied to the silica aerogel sheet, because the surface A has a large number (distribution) of voids or has a large surface roughness, and can suppress powder falling to the bottom. In addition, since surface A has a predetermined shape and / or is formed of fibers, it can increase the adhesion to a film, etc., and therefore suppress the peeling of the silica aerogel from the film, etc. when stress, vibration, etc. is applied to the silica aerogel sheet, and as a result, suppress the powder falling to the bottom.
[0041] On the other hand, the other surface (hereinafter referred to as surface B), which has a relatively small number (distribution) of voids or a relatively small surface roughness, is subjected to less stress and vibration than the other surface B. This makes it difficult for the silica aerogel that is physically and chemically bonded to the fibers to peel off. In light of this, the number (distribution) of voids that can cause powder to fall off or the surface roughness can be reduced.
[0042] As described above, by varying the properties of the sheet surface, powder falling off of the sheet as a whole can be suppressed, and therefore a decrease in the heat insulating performance can be suppressed.
[0043] -Number of holes- The number of pores is different between surfaces A and B. The ratio of the number of pores on surface A to the number of pores on surface B is preferably 1.3 or more, 2.0 or more, more preferably 2.2 or more, even more preferably 2.7 or more, or 4.0 or more. The upper limit is preferably 9.0 or less, more preferably 8.0 or less, and even more preferably 7.0 or less. Therefore, the preferred range of the ratio is 1.3 or more, more preferably 1.3 to 9.0, 1.3 to 8.0, 1.3 to 7.0, 2.0 to 9.0, 2.0 to 8.0, 2.0 to 7.0, 2.2 to 9.0, 2.2 to 8.0, 2.2 to 7.0, 2.7 to 9.0, 2.7 to 8.0, 2.7 to 7.0, 4.0 to 9.0, 4.0 to 8.0, or 4.0 to 7.0. As a result, surface B can better exhibit its insulating properties by preventing powder from falling off, while surface A can better exhibit its insulating properties by preventing powder from falling off and improving adhesion.
[0044] The number of holes on surface A is preferably 25,000 / m 2 More preferably, 35,000 pieces / m 2 More preferably, 50,000 pieces / m 2 This allows the powder falling off the sheet surface to be captured and the powder falling off to be suppressed. The upper limit is preferably 225,000 particles / m 2 Less than or equal to 200,000 pieces / m 2 Less than 150,000 pieces / m, more preferably 150,000 pieces / m 2 This makes it possible to prevent the pores themselves from falling off the sheet surface and to prevent powder falling off. Therefore, the density is preferably 25,000 to 225,000 pores / m 2 , more preferably 35,000 to 200,000 pieces / m 2 , and more preferably 50,000 to 150,000 pieces / m 2 It is.
[0045] The number of pores on surface B is preferably 10,000 / m 2 More preferably, 20,000 pieces / m 2 This allows the powder falling off the sheet surface to be captured and the powder falling off to be suppressed. The upper limit is preferably 50,000 particles / m 2 Less than or equal to 30,000 pieces / m2 This makes it possible to prevent the pores themselves from falling off the sheet surface and to prevent powder falling off. Therefore, the density is preferably 10,000 to 50,000 pores / m 2 , more preferably 20,000 to 30,000 pieces / m 2 It is.
[0046] The number of voids can be counted by the following method. The sheet is cut into 15cm x 15cm pieces, and five arbitrary positions on the surface of the sheet are photographed using a digital camera (e.g., Canon PowerShot SX720 HS). The photographed image is cut into 2cm x 2cm (200 pixels x 200 pixels) images using image processing software (e.g., ImageJ), and the binarization function of ImageJ is used to binarize areas with a brightness of 125 or less as voids (for example, examples of binarization of surfaces A and B are shown in Figures 1 and 2, respectively). Next, particles of 4 pixels^2 or less are removed as noise using the particle analysis function of ImageJ, and the number of voids is counted. In this way, the average value of the five locations is calculated and used as the number of voids. The pores may be covered with glass fibers or the like, and include pores that penetrate from the front surface to the back surface. The pores counted under the above conditions are those with a diameter of more than 0.2 μm.
[0047] The degree of unevenness of the sheet surface can be expressed by the surface roughness Sa (arithmetic mean height). The lower limit of the surface roughness of surface A is preferably 60 μm or more, more preferably 65 μm or more, and even more preferably 70 μm or more, 80 μm or more, or 90 μm or more. This makes it possible to capture powder falling off the sheet surface and suppress powder falling off.
[0048] The upper limit of the surface roughness of surface A is preferably 130 μm or less, more preferably 120 μm or less, even more preferably 110 μm or less, or 100 μm or less. This can prevent the voids themselves from falling off the sheet surface and prevent powder from falling off. Therefore, the surface roughness of surface A is preferably 60 to 130 μm, more preferably 65 to 110 μm, even more preferably 70 to 100 μm, 80 to 100 μm, or 90 to 100 μm.
[0049] The lower limit of the surface roughness of surface B is preferably 20 μm or more, 25 μm or more, more preferably 30 μm or more, and even more preferably 40 μm or more. This allows the powder falling off the sheet surface to be captured and the powder falling off to be suppressed. The upper limit of the surface roughness of surface B is preferably less than 60 μm, more preferably 55 μm or less, and even more preferably 50 μm or less. This allows the voids themselves to be suppressed from falling off the sheet surface and the powder falling off to be suppressed. Therefore, the surface roughness of surface B is preferably less than 20 to 60 μm, less than 25 to 60 μm, more preferably less than 30 to 60 μm, and even more preferably 30 to 50 μm, 40 to 50 μm, or 40 to 45 μm.
[0050] The surface roughness of surface A is preferably larger than that of surface B, and the difference between the two (AB) is usually 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, 40 μm or more. The upper limit is not particularly limited, but is, for example, 100 μm or less, 90 μm or less, or 80 μm or less.
[0051] The ratio (A / B) of the surface roughness of surface A to the surface roughness of surface B is preferably 1.3 or more, more preferably 1.5 or more, even more preferably 2.3 or more, 2.7 or more, or 4.5 or more. The upper limit is usually 7.0 or less, preferably 6.5 or less, more preferably 6.0 or less. Therefore, it is preferably 1.3 or more, more preferably 1.3 to 7.0, 1.3 to 7.0, 1.3 to 6.5, 1.3 to 6.0, 1.5 to 7.0, 1.5 to 6.5, 1.5 to 6.0, 2.3 to 7.0, 2.3 to 6.5, 2.3 to 6.0, 2.7 to 7.0, 2.7 to 6.5, 2.7 to 6.0, 4.5 to 7.0, 4.5 to 6.5, or 4.5 to 6.0.
[0052] Surface roughness Sa is the arithmetic mean height, and is the average value of values measured at any five points in accordance with ISO 25178. Surface roughness Sa of surfaces A and B can be measured by observation using a microscope (for example, Keyence's "One-shot 3D shape measuring instrument VR-6000"). A measurement sheet of 15 cm x 15 cm is prepared, and weights of 0.13 kg are placed on both ends at intervals of 3 cm when viewed from the front direction to flatten the sheet surface. The image of the center range (18 mm x 24 mm) taken at 12x magnification is used to calculate the surface roughness Sa using the surface roughness mode in the analysis program (program name KEYENCE VR-6000 analysis application).
[0053] [3. Manufacturing method of heat insulation sheet] One method for manufacturing an insulating sheet is, for example, to dissolve a silica material in a solvent to prepare a reaction liquid (sol), which is then gelled, and impurities such as the solvent and unreacted materials are removed from the resulting wet gel, which is then coated and dried within a frame.
[0054] Examples of silica materials include methyltrimethoxysilane (MTMS), trimethylmethoxysilane (TMS), dimethyldimethoxysilane (DMS), trimethylethoxysilane, dimethyldiethoxysilane (DMDS), methyltriethoxysilane (MTES), ethyltriethoxysilane (ETES), diethyldiethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane (PhTES), hexamethyldisilazane, and hexaethyldisilazane.
[0055] Examples of the solvent include water, methanol, ethanol, isopropanol, ethyl acetate, ethyl acetoacetate, acetone, dichloromethane, and tetrahydrofuran. Of these, an acidic aqueous solution is preferred, and an aqueous acetic acid solution is more preferred. The reaction solution usually contains a hydrolyzable compound (e.g., urea), and may contain a surfactant (e.g., aliphatic ammonium, alkylbenzylammonium) as needed. When preparing the sol, ice cooling and stirring may be performed as needed. Drying is usually performed by supercritical drying, but drying at normal pressure may also be used. Supercritical drying is performed by exchanging a solvent (e.g., alcohol such as 2-propanol or ethanol) with a supercritical fluid (e.g., supercritical carbon dioxide gas) once or twice or more times. Pressurization may be performed during drying as necessary. This allows the thickness of the sheet to be uniform. The timing of adding the fibers is preferably during the stage from preparation of the reaction liquid to gelation (for example, by immersing a nonwoven fabric of the fibers in the reaction liquid once or more than once) and / or drying, and it is more preferable to immerse the fibers in the reaction liquid (sol). The gelation method is not particularly limited, and can be performed, for example, by leaving the reaction liquid still (for example, leaving it still in a sealed device, preferably leaving it still in a sealed device under heating (for example, 50°C or higher, 60°C or higher)), adding a catalyst, irradiating with ultraviolet light, etc., and leaving it still is preferable. The void ratio and surface roughness of the sheet surface can also be adjusted by changing the gelation conditions and the fiber addition conditions (number of times of impregnation). In this specification, silica aerogel refers not only to silica aerogel in the narrow sense (silica aerogel obtained by supercritical drying), but also to silica aerogel obtained by other drying methods (e.g., xerogel (produced by drying at normal pressure), cryogel (produced by freeze-drying), and ambigel (produced by drying under ambient pressure)). At any stage of production, holes are formed by a method such as perforation, which allows the hole ratio and surface roughness of the sheet surface to be adjusted.
[0056] In addition, a hydrophobization treatment (for example, a treatment of converting a silica surface functional group (for example, a hydroxyl group) into a hydrophobic trimethylsilyl group) may be performed at any stage, and is preferably performed before the drying step. The hydrophobization treatment can be performed by adding a hydrophobizing agent such as a trimethylsilylating agent. When the hydrophobization treatment is performed, the content of the hydrophobized silica in the entire aerosilica gel sheet obtained through the treatment is preferably 5% by mass or more, more preferably 7% by weight or more, and the upper limit is preferably 30% by weight or less, more preferably 25% by weight or less. In addition, the weight ratio of the hydrophobized silica to the non-hydrophobized silica (hydrophobized / non-hydrophobized) is preferably 0.1 or more, more preferably 0.2 or more, and the upper limit is preferably 1.5 or less, more preferably 1.2 or less, and even more preferably 1.0 or less.
[0057] [4. Other layers] The heat insulating sheet may form a laminate (heat insulating material) together with other members, such as a film, an elastic layer, and an adhesive layer.
[0058] [4.1 Film] The heat insulating material may further have a film that covers (seals) at least one of the surfaces (preferably only surface A, or both surfaces A and B). This can further suppress powder falling off. In particular, it is preferable to cover surface A or to cover both surfaces. This can more efficiently suppress powder falling off. This effect can be further enhanced by arranging sheet surface A on the side between the cells that is subjected to greater stress.
[0059] Examples of polymer films include films made of polyimide, polycarbonate, PET, p-phenylene sulfide, polyetherimide, crosslinked polyethylene, flame-retardant chloroprene rubber, polyvinyl denfluoride, rigid polyvinyl chloride, polybutylene terephthalate, PTFE, PFA, FEP, ETFE, rigid PCV, flame-retardant PET, polystyrene, polyethersulfone, polyamideimide, polyacrylonitrile, polyethylene, polypropylene, polyamide, and the like.
[0060] [4.2 Adhesive layer] When other members are provided on the heat insulating material, an adhesive layer may be further included. The adhesive layer can be made of a material capable of adhering the heat insulating material sheet to other members. Examples of materials for the adhesive layer include epoxy resin, phenolic resin, acrylic resin, melamine resin, vinyl acetate resin, silicone resin, urethane resin, polyethylene, and polypropylene.
[0061] [4.3 Elastic material layer] The elastic layer is a layer for alleviating stress generated in the heat insulating sheet and applying a certain compression load to the battery cell. In particular, by covering surface A, the stress alleviation effect can be further enhanced. This effect can be further enhanced by disposing surface A covered with the elastic layer on the side between the cells that receives a larger stress. The material of the elastic layer may be either natural rubber or synthetic rubber, and is preferably made mainly of, for example, polyisoprene, hydrogenated polyisoprene, polybutadiene, styrene-butadiene copolymer, isobutylene-isoprene copolymer, ethylene-propylene copolymer, ethylene-propylene-diene terpolymer (EPDM), or silicone. The shape of the elastic body is not particularly limited, and the shape of its surface is not particularly limited, but it is preferable that the surface that does not contact the heat insulating sheet (for example, the surface that contacts the cell) has a protruding portion such as unevenness. This can further enhance the powder fall prevention effect by alleviating the stress of the sheet.
[0062] [4.4 Lamination method] The method of laminating other layers onto the sheet is not particularly limited, and includes a method of laminating other layers required for the heat insulating sheet. The lamination step can be, for example, a method of applying an adhesive to at least one surface of the heat insulating sheet (using equipment or tools such as a blade coater, a bar coater, a die coater, a comma coater (registered trademark), a roll coater, or a brush, as necessary), drying (for example, at 80 to 180°C, several minutes to several tens of minutes), or a method of adhering other layers that have been previously prepared via an adhesive or adhesive layer. In the case of a film, for example, a method of attaching a film to the surface of a sheet with an adhesive or the like, or a method of storing the film in a bag-shaped film can be included.
[0063] [5. Uses of insulation sheets] The heat insulating sheet can show a good balance between heat insulating properties. Therefore, it can be used as a heat insulating sheet between battery cells for automobiles. When used between battery cells for automobiles, the sheet can be placed between the cells.
[0064] It is preferable to place surface A of the sheet facing the side that receives greater stress, such as the side where stress occurs due to battery expansion, the vibration source side, the side where motor vibration is large, etc. This makes it possible to efficiently suppress powder falling off and maintain adhesion, while surface B can maintain its heat insulating properties and adhesion, thereby providing heat insulating performance overall. EXAMPLES
[0065] The present invention will be described with reference to examples. Note that the following examples are merely illustrative of the present invention and are not intended to limit the present invention.
[0066] Example 1 (Preparation of glass fiber reinforced aerogel sheet) As a cationic surfactant, 1.00 g of cetyltrimethylammonium bromide (also known as hexadecyltrimethylammonium bromide, manufactured by Nacalai Tesque, Inc., hereinafter abbreviated as "CTAB") was dissolved in 10.00 g of 0.01 mol / L acetic acid aqueous solution, which is an acidic aqueous solution, and then 0.50 g of urea (manufactured by Nacalai Tesque, Inc.) was added as a hydrolyzable compound and dissolved. 5.0 mL of methyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., LS-530 (specific gravity: 0.95), hereinafter abbreviated as "MTMS") was added as a silica material to this acidic aqueous solution, and the mixture was stirred and mixed for 30 minutes under ice cooling to cause a hydrolysis reaction of MTMS and generate a sol. The sol was then impregnated into a perforated glass fiber nonwoven fabric (manufactured by Nippon Glass Fiber Industry, Nitigura Mat, MNA-300-1000-30m, thickness 3mm) placed on a polypropylene film (thickness 50 μm). The gel was allowed to stand at 60°C for 3 hours in a sealed container to gel. The gel was then allowed to stand for another 96 hours in a sealed container to mature. The gel was then removed from the sealed container and immersed in 2-propanol to perform solvent replacement. This operation was carried out for 24 hours at 60°C the first time, and for 48 hours at 60°C after replacing with fresh 2-propanol.
[0067] The aerogel sheet was then supercritically dried under the following conditions: The inside of a 400 mL autoclave was filled with 2-propanol, and the aerogel sheet after the solvent exchange was placed inside. The lid was closed, and liquefied carbon dioxide was pumped in to bring the pressure to approximately 882 N / cm. 2 (approx. 90kgf / cm 2 ) while maintaining the temperature, the first liquid phase replacement operation was carried out (time required: 1.5 hours).
[0068] After the first liquid phase replacement was completed, the valve was closed and the pressure was maintained while liquefied carbon dioxide was diffused into the gel for 17.5 hours. After that, the pressure was increased to about 882 N / cm 2 (approx. 90kgf / cm 2 ) and a second liquid phase replacement was carried out (required time: 1 hour). After the second liquid phase substitution was completed, the valve was closed and the pressure was maintained as in the first step, and liquefied carbon dioxide was allowed to diffuse into the gel for five hours. After that, as with the first liquid phase replacement, the pressure was about 882N / cm 2 (approx. 90kgf / cm 2 ) was maintained, and the third liquid phase replacement was carried out in the same manner (required time: 0.75 hours).
[0069] After the third liquid phase replacement was completed, the valve was closed and the autoclave was heated from room temperature to 80° C. over 1.5 hours. After reaching 80℃, 4.9N / cm 2 min(0.5kgf / cm 2 The pressure was reduced at a rate of 1.0 psi (min). After reaching atmospheric pressure, the autoclave was cooled to room temperature over 2 hours. Thereafter, the autoclave was opened, the aerogel sheet was taken out, and the supercritical drying was terminated. In this way, a glass fiber reinforced aerogel sheet (thickness: 3 mm) of Example 1 was produced. The side in contact with the film is side B.
[0070] Example 2 (Preparation of Glass Fiber Reinforced Aerogel Sheet 2) The resulting sol was heated at 60°C for 0.5 hours, and then impregnated into a glass fiber nonwoven fabric and allowed to stand in a sealed container at 60°C for 2.5 hours to gel. In the same manner as in Example 1, except that, a glass fiber reinforced aerogel sheet of Example 2 was produced.
[0071] Example 3 (Preparation of Glass Fiber Reinforced Aerogel Sheet 3) The resulting sol was heated at 60°C for 1 hour, and then impregnated into a glass fiber nonwoven fabric and allowed to stand in a sealed container at 60°C for 2 hours to gel. In the same manner as in Example 1, except that, a glass fiber reinforced aerogel sheet of Example 3 was produced.
[0072] Example 4 (Preparation of Glass Fiber Reinforced Aerogel Sheet 4) A glass fiber reinforced aerogel sheet of Example 4 was produced in the same manner as in Example 2, except that the nonwoven fabric impregnated with the sol was sandwiched between polypropylene films and squeegeeed from the A-side, and then the polypropylene film on the A-side was peeled off.
[0073] Example 5 (Preparation of Glass Fiber Reinforced Aerogel Sheet 5) A glass fiber-reinforced aerogel sheet of Example 5 was produced in the same manner as in Example 2, except that the glass fiber nonwoven fabric was perforated from the B-side.
[0074] Example 6 The nonwoven fabric impregnated with the sol was left to stand in a sealed container at 60° C. for 1 hour, then removed from the sealed container and impregnated with the sol again. In the same manner as in Example 1, except that, a glass fiber reinforced aerogel sheet of Example 6 was produced.
[0075] Example 7 A glass fiber-reinforced aerogel sheet of Example 7 was produced in the same manner as in Example 6, except that a nonwoven fabric with fluffed A-side was used.
[0076] Example 8 A glass fiber reinforced aerogel sheet of Example 8 was produced in the same manner as in Example 1, except that the nonwoven fabric impregnated with the sol was sandwiched between polypropylene films and squeegeeed from the A-side, and then the polypropylene film on the A-side was peeled off.
[0077] Example 9 A glass fiber reinforced aerogel sheet of Example 9 was produced in the same manner as in Example 8, except that a nonwoven fabric with fluffed surface B was used.
[0078] Example 10 The nonwoven fabric impregnated with the sol was left to stand in a sealed container at 60° C. for 1 hour, then removed from the sealed container and impregnated with the sol again. In the same manner as in Example 3, except that, a glass fiber reinforced aerogel sheet of Example 10 was produced.
[0079] Comparative Example 1 The resulting sol was heated at 60°C for 2 hours, and then impregnated into a glass fiber nonwoven fabric and allowed to stand in a sealed container at 60°C for 1 hour to gel. In the same manner as in Example 1, except that, a glass fiber reinforced aerogel sheet of Comparative Example 1 was produced.
[0080] Comparative Example 2 A glass fiber reinforced aerogel sheet of Comparative Example 2 was produced in the same manner as in Example 1, except that the sol was impregnated into a glass fiber nonwoven fabric (chopped strand mat, MC-600A, manufactured by Nitto Boseki Co., Ltd., with a fluffed B-side) so as to have a thickness of 3 mm, and the sol was allowed to stand in a sealed container at 60°C for 3 hours to cause gelation.
[0081] Comparative Example 3 The sol was produced, and a glass fiber nonwoven fabric (Nittobo, chopped strand mat, MC-600A, thickness 1 mm) was layered to a thickness of 3 mm and impregnated therein. The fabric was sandwiched between polypropylene films and squeegeeed from the A-side side. The film on the A-side side was then peeled off, the fabric was impregnated with the sol, and the fabric was sandwiched again between polypropylene films. In the same manner as in Example 4, except for this, a glass fiber reinforced aerogel sheet of Comparative Example 3 was produced.
[0082] Example 11 The produced sol was used to prepare a glass fiber-reinforced aerogel sheet of Example 11 in the same manner as in Comparative Example 1, except that the A-side was fluffed.
[0083] Example 12 A glass fiber reinforced aerogel sheet of Example 12 was produced in the same manner as in Example 2, except that the sol was impregnated into a nonwoven glass fiber fabric (chopped strand mat, MC-600A, manufactured by Nitto Boseki, thickness 1 mm) in a thickness of 3 mm.
[0084] [Physical property test methods] -Evaluation method for "powder shedding"- (1) A measurement sheet (prepared by cutting to a surface size of 5×5 cm) was coated with a PET film (thickness 50 μm) and bonded to a rubber sheet to prepare a sample. The rubber sheet has a structure in which a plurality of ridge unit (in the cross-section, having a base width of 10.86 mm, a height of about 7 mm, a 60° taper, and a convex portion extending in the width direction and a concave portion around it, and the width including the concave and convex portions is about 20.5 mm) are connected. The measurement sheet and the rubber sheet were arranged so that the concave portion of the ridge is on the A surface side. In a vibrator equipped with a jig consisting of a pair of metal plates and a powder receiver, the sample was sandwiched (stood up) between the metal plates so that the surface of the sample is in a substantially vertical direction, pressurized and fixed to a state where the sample is compressed by 50%, and given vibrations of 3G / 15 Hz × 800,000 times. (2) Thereafter, with the sample standing in a substantially horizontal direction, the film was peeled off, and the amount of aerogel falling on each of the A and B surfaces was visually confirmed. It was judged which of the evaluation criteria in (3) the amount of aerogel falling on surface A corresponded to that of surface A in Comparative Example 1, and for surface B corresponded to that of surface B in Comparative Example 2. (3) Evaluation criteria (Surface A is evaluated based on surface A of Comparative Example 1, and surface B is evaluated based on surface B of Comparative Example 2) For those with the amount of aerogel falling less than or equal to 1 / 3 of the standard... A For those with the amount of aerogel falling exceeding 1 / 3 and less than or equal to 1 / 2 of the standard... B For those with the amount of aerogel falling exceeding 1 / 2 of the standard... C
[0085] - Method for evaluating "adhesion" - Samples with an adhesive tape (manufactured by Sekisui Chemical Co., Ltd., thickness 0.15 mm, green) attached to the A and B surfaces of the heat insulation material sheet were prepared. Using a tabletop tensile testing machine ("AGS-1kNG" manufactured by Minebea), a 180° peel test (conforming to JIS Z 0237:2009, tensile speed 300 mm / min) was performed at the interface between the heat insulation material sheet and the adhesive tape, and the peel force was measured and taken as the interfacial adhesion force between the layers. <Standard for A surface> Those with a tensile load of 5 N / 25 mm or more were rated as having good adhesion "A", those with a tensile load of 0.5 - 5 N / 25 mm were rated as having adhesion "B", and those with a tensile load of less than 0.5 N / 25 mm were rated as having poor adhesion "C". <Reference for the B side> Those with a tensile load of 0.5 N / 25 mm or more were rated as having good adhesion "A", and those with a tensile load of less than 0.5 N / 25 mm were rated as having poor adhesion "C".
[0086] - Evaluation method for "Comprehensive Evaluation"- Based on the following criteria, a comprehensive evaluation was conducted. When all are A... ◎ When there are A and B... 〇 When there is even one C... ×
[0087] [Test method for the surface properties of the sheet] - Surface roughness- The surface roughness Sa was measured by the following method. The sheet was cut into a size of 15 cm × 15 cm, and with weights of 0.13 kg placed at both ends at an interval of 3 cm when viewed from the front to flatten the sheet surface. In the central area (18 mm × 24 mm) of the sheet measurement surface, the average value of the values calculated for any 5 locations in the surface roughness mode of the analysis program (program name: KEYENCE VR-6000 analysis application) of the image taken at a magnification of 12 times using a microscope (Keyence's "One Shot 3D Shape Measuring Machine VR-6000") was defined as the surface roughness Sa.
[0088] - Number of pores per unit area- The number of voids was measured by the following method. The sheet was cut into 15cm x 15cm pieces, and the surface of the sheet was photographed at 5 random positions using a digital camera (Canon PowerShot SX720 HS). The photographed image was cut into 2cm x 2cm (200 pixels x 200 pixels) images using image processing software (ImageJ), and the areas with a brightness of 125 or less were binarized as voids using the binarization function of ImageJ. Next, particles of 4 pixels^2 or less were removed as noise using the particle analysis function of ImageJ, and the number of voids was counted, and the average value of the 5 locations was calculated. The pores may be covered with glass fibers or the like, and include pores that penetrate from the front surface to the back surface. The pores counted under the above conditions are those with a diameter of more than 0.2 μm.
[0089] [Table 1]
[0090] [Table 2]
[0091] [Table 3]
[0092] [Table footnotes] In the table, the number of voids is the number of voids observed within an area of 2 cm × 2 cm (200 pixels × 200 pixels) and the number of voids observed within 1 m 2 The number of pieces per unit (numbers in parentheses) is also listed.
[0093] The overall evaluation of Comparative Examples 1 and 2, in which the number of pores was less than 1.3, was x, whereas the overall evaluation of Examples 1 to 10, in which the number of pores was 1.3 or more, was ◯ or ◎. Moreover, the overall evaluation of Examples 11 and 12, in which the difference in surface roughness was 30 or more, was ◯.
[0094] The number of voids on surface A can be considered as follows. Comparing Examples 1 and 2, the powder shedding property of Example 1 on surface A was rated B, whereas Example 2, which had a relatively small number of voids on surface A, was rated A. Comparing Examples 3 and 10 with Example 2, the powder shedding property of Examples 3 and 10 was rated B, whereas Example 2, which had a relatively large number of voids on surface A, was rated A. These results show that a smaller number of voids on surface A tends to suppress the voids themselves from falling off, whereas a larger number of voids tends to make it easier to capture powder.
[0095] The number of voids on surface B is considered as follows. Comparing Examples 4 and 2, the powder shedding properties of surface B in Example 4 were rated B, whereas Example 2, which had a relatively large number of voids on surface B, was rated A. Comparing Examples 5 and 10 and 2, the powder shedding properties of surface B in Examples 5 and 10 were rated B, whereas Example 2, which had a relatively large number of voids on surface B, was rated A. This result shows that, like surface A, with respect to surface B, a smaller number of voids tends to suppress the voids themselves from falling off, whereas a larger number of voids tends to make it easier to capture powder.
[0096] The surface roughness of surface A is considered as follows. Comparing Examples 6 and 2, the powder shedding property of surface A in Example 6 was rated B, whereas Example 2, in which the surface roughness of surface A was relatively large, was rated A. Comparing Examples 7 and 2, the powder shedding property of Example 7 was rated B, whereas Example 2, in which the surface roughness of surface A was relatively small, was rated A. These results show that a surface A with a large surface roughness tends to be able to capture powder by voids, whereas a surface with a small surface roughness tends to be able to suppress the voids themselves from falling off.
[0097] The surface roughness of surface B is considered as follows. Comparing Examples 8 and 2, the powder shedding property of surface B in Example 8 was rated B, whereas in Example 2, where the surface roughness of surface B was relatively large, it was rated A. Comparing Examples 9 and 2, the powder shedding property of Example 9 was rated B, whereas in Example 2, where the surface roughness of surface A was relatively small, it was rated A. These results show that, like surface A, with respect to surface B, a larger surface roughness of surface B tends to enable the voids to capture powder, whereas a smaller surface roughness tends to suppress the voids themselves from falling off.
[0098] The above results show that the heat insulating sheet of the present invention can exhibit good heat insulating properties and is useful as a heat insulating material between battery cells in automobiles.
Claims
1. Contains silica aerogel and fibers, A plurality of projections and recesses are provided on one surface and the other surface in the thickness direction. The ratio of the surface roughness of one surface to the surface roughness of the other surface is 1.3 or more; The one surface is disposed on a side subjected to a larger stress or vibration, and the other surface is disposed on a side subjected to a smaller stress or vibration, Insulation sheet between battery cells for electric vehicles.
2. The sheet according to claim 1 , wherein a difference between the surface roughness Sa of said one surface and the surface roughness Sa of said other surface is 10 μm or more.
3. The sheet according to claim 1 or 2, wherein a difference between a surface roughness Sa of the one surface and a surface roughness Sa of the other surface is 30 μm or more.
4. The sheet according to claim 1 or 2, wherein the surface roughness Sa of the one surface is 60 μm or more.
5. The sheet according to claim 1 or 2, wherein the surface roughness Sa of the one surface is 80 to 100 μm.
6. The sheet according to claim 1 or 2, wherein the other surface has a surface roughness Sa of less than 60 μm.
7. The sheet according to claim 1 or 2, wherein the surface roughness Sa of the other surface is 30 to 50 μm.
8. The number of holes on said one surface is 25,000 to 225,000 / m 2 3. The sheet according to claim 1 or 2, wherein the number of voids is the number of voids having a diameter greater than 0.2 μm.
9. The number of holes on the other surface is 10,000 to 50,000 / m 2 3. The sheet according to claim 1 or 2, wherein the number of voids is the number of voids having a diameter greater than 0.2 μm.
10. Contains silica aerogel and fibers, A plurality of projections and recesses are provided on one surface and the other surface in the thickness direction. the ratio of the surface roughness of one surface to the surface roughness of the other surface is 2.3 to 4.4; The difference in surface roughness of one surface relative to the surface roughness of the other surface is 30 to 100 μm. Insulation sheet between battery cells for electric vehicles.
11. 11. The sheet according to claim 1, further comprising a film covering at least a portion of said one surface and said other surface.
12. 11. The sheet according to claim 1, further comprising an elastic layer laminated on at least a portion of the one surface and the other surface.
13. 11. The sheet according to claim 1, further comprising a film covering said one surface and said other surface, and an elastic layer laminated on said one surface or said other surface via the film.
Citation Information
Patent Citations
Heat insulation material and apparatus using the same
JP2018091480A
Thermal insulation elastic member
JP2023035097A
Method for manufacturing heat transfer suppressing sheet, heat transfer suppressing sheet, and assembled battery
JP2023132944A
Fire spread prevention sheet and battery including the same
JP2024061698A
Heat insulating / fireproof sheet, and battery pack and battery module package using the same
JP2024097328A